Comparative Genomics Analysis of Ciliates Provides Insights on the Evolutionary History Within “Nassophorea–Synhymenia–Phyllopharyngea” Assemblage - Pan, Bo; Chen, Xiao; Hou, Lina; Zhang, Qianqian; Qu, Zhishuai; Warren, Alan; Miao, Miao (Frontiers in Microbiology, 2019)
Ciliated protists (ciliates) are widely used for investigating evolution, mostly due to their successful radiation after their early evolutionary branching. In this study, we employed high-throughput sequencing technology to reveal the phylogenetic position of Synhymenia, as well as two classes Nassophorea and Phyllopharyngea, which have been a long-standing puzzle in the field of ciliate systematics and evolution. We obtained genomic and transcriptomic data from single cells of one synhymenian (Chilodontopsis depressa) and other six species of phyllopharyngeans (Chilodochona sp., Dysteria derouxi, Hartmannula sinica, Trithigmostoma cucullulus, Trochilia petrani, and Trochilia sp.). Phylogenomic analysis based on 157 orthologous genes comprising 173,835 amino acid residues revealed the affiliation of C. depressa within the class Phyllopharyngea, and the monophyly of Nassophorea, which strongly support the assignment of Synhymenia as a subclass within the class Phyllopharyngea. Comparative genomic analyses further revealed that C. depressa shares more orthologous genes with the class Nassophorea than with Phyllopharyngea, and the stop codon usage in C. depressa resembles that of Phyllopharyngea. Functional enrichment analysis demonstrated that biological pathways in C. depressa are more similar to Phyllopharyngea than Nassophorea. These results suggest that genomic and transcriptomic data can be used to provide insights into the evolutionary relationships within the "Nassophorea-Synhymenia-Phyllopharyngea" assemblage.